2013
DOI: 10.1002/ijc.28375
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of endogenous ICAM‐1 reduces ovarian cancer cell growth in the absence of immune cells

Abstract: Ovarian cancer is a difficult-to-treat cancer with a 5-year survival rate of only~45%, due to late diagnosis and therapy resistance. In need of new therapeutic approaches, induction of intercellular adhesion molecule (ICAM)-1 expression might be of interest, since the expression of ICAM-1 is lower in ovarian cancer cells compared with healthy ovarian cells and correlated with decreased tumorigenicity. Whereas ICAM-1 expression on tumor cells is of importance for attracting immune cells, ICAM-1 might also induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
0
22
1
Order By: Relevance
“…The CD54-31Opt was chosen because it was shown to effectively target the ICAM1 promoter, altering transcription levels when fused to transcriptional activators or repressors [50], [51]. Additionally, fusion of CD54-31Opt to Ten-Eleven Translocation 2 enzyme resulted in a small, observable amount of demethylation around the target site, correlating with a 2-fold upregulation in ICAM1 transcription [52].…”
Section: Resultsmentioning
confidence: 99%
“…The CD54-31Opt was chosen because it was shown to effectively target the ICAM1 promoter, altering transcription levels when fused to transcriptional activators or repressors [50], [51]. Additionally, fusion of CD54-31Opt to Ten-Eleven Translocation 2 enzyme resulted in a small, observable amount of demethylation around the target site, correlating with a 2-fold upregulation in ICAM1 transcription [52].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, expression of ICAM1 is highly variable in cancer, being up-regulated in breast, gastric, melanoma, gall bladder, and colon cancers [45], [46] and down-regulated in ovarian [47] and gastric [48] cancers. MCAM is another IgSF-CAM that was uniquely and highly expressed in the MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In melanoma and gastric cancer, ICAM1 expression was associated with an increase in metastases [79, 80]. This can be explained by ICAM1-mediated activation of leukocytes and induction of cell migration [81]. On the other hand, immunohistochemistry studies reported better prognosis for patients with ICAM1-positive tumors (including lymphoma, ovarian, colorectal, head and neck cancers) [8284].…”
Section: Discussionmentioning
confidence: 99%